OPTIMIZATION OF MECHANICAL STRENGTH AND MICROSTRUCTURE ON AUSTEMPERING ZINC HEAT TREATMENT IN LATERITIC NICKEL STEELS - Satrio Herbirowo; Setyo Hartadi; Rahmat D. Widodo; Bintang Adjiantoro (Jurnal Sains Materi Indonesia, 2019)
The development of lateritic steel is currently being discussed by various research institutions. It is not separated from the potential of laterite-based steel into national steel. This research using austempering heat treatment process with holding time variation for 30, 60, and 90 minutes with Zn (Zinc) element from melting ingot with 90% purity for cooling media. The characterization of laterite steel is done by hardness testing, impact resistance, microstructure, scanning electron microscopy, and energy dispersive spectroscopy. The results showed that the impact resistance value decreased 8.46%, which was initially 209 J to 191.3 J. Besides, the hardness value increased 36, 58% of which was originally 164 HV to 224 HV. Judging from its physical properties, the microstructure formed bainite ferrite perlite at holding time 90 minutes while the fracture is included into the ductile fracture because there are dimple holes showed dark and opaque